Evaluating the Accountability of Provincial Government in Achieving SDGs Through Green Accounting: A Case Study of NTB Province - Kartikasari, Nungki; Anggara, Jaka (Journal of Finance, Economics and Business, 2024)
The Provincial Government of Nusa Tenggara Barat (NTB) has made significant efforts toward achieving Sustainable Development Goals (SDGs) by implementing green projects such as renewable energy initiatives, waste management, and carbon emission reduction programs. However, transparency in non-financial reporting, particularly regarding environmental and social impacts, remains insufficient. This study evaluates NTB’s accountability in achieving SDG targets through green accounting and assesses the transparency and effectiveness of related financial and non-financial reporting. Using data from 2020 to 2023, analyzed through a quantitative descriptive approach, findings highlight substantial progress in waste reduction, renewable energy, and carbon emissions. Nevertheless, transparency in non-financial reporting is inadequate, limiting accountability. Adopting standards such as the Global Reporting Initiative (GRI) is recommended to enhance sustainability reporting.